2010
DOI: 10.1667/rr2195.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles in Mouse Liver after Long-Term Low-Dose-Rate Irradiation with Gamma Rays

Abstract: Changes in gene expression profiles in mouse liver induced by long-term low-dose-rate γ irradiation were examined by microarray analysis. Three groups of male C57BL/6J mice were exposed to whole-body radiation at dose rates of 17-20 mGy/day, 0.86-1.0 mGy/day or 0.042-0.050 mGy/day for 401-485 days with cumulative doses of approximately 8 Gy, 0.4 Gy or 0.02 Gy, respectively. The gene expression levels in the livers of six animals from each exposure group were compared individually with that of pooled sham-irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Although some LDR gene profiling studies have been reported, these have been aimed towards the effects of occupational or environmental exposures, and have used mice exposed to much lower dose rates and/or total doses not of concern for radiological triage (3639). Studies of humans occupationally exposed over many years to low total doses (40, 41) have also been published.…”
Section: Discussionmentioning
confidence: 99%
“…Although some LDR gene profiling studies have been reported, these have been aimed towards the effects of occupational or environmental exposures, and have used mice exposed to much lower dose rates and/or total doses not of concern for radiological triage (3639). Studies of humans occupationally exposed over many years to low total doses (40, 41) have also been published.…”
Section: Discussionmentioning
confidence: 99%
“…exposed mice to a range of low doses of external beam 57 Co at a dose rate of approximately 0.003 mGy/min (35), or to protons at approximately 0.02 mGy/min (36), and reported significant changes in the expression of several genes immediately after exposure. In another study, exposure to a range of low-dose rates at or below 0.013 mGy/min for more than 400 days resulted in small changes in a small number of genes (14). Another study exposed mice for 1–40 days to external gamma rays delivered at a constant 2.8 mGy/min (37) and reported a consistent overexpression of some p53 regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, although in these studies, the doses and the dose rates met the criteria of the United Nations Scientific Committee on the Effects of Atomic Radiation (13) for being either LD (≤200 mGy) or LDR (≤6 mGy/h), the effects of the LD and LDR irradiation on gene expression were not elucidated. In line with these studies, Taki et al (14) discovered that heat-shock proteins and DNA repair genes were expressed in LDR-irradiated (0.032-12 μGy/min; final dose, 0.02-8 Gy) C57BL/6J mice, whereas Uehara et al (15) found that obesity-and tumorigenesis-related genes were downregulated in the livers of LDR-irradiated (0.042-20 mGy/d; final dose, 0.02-8 Gy) C57BL/6J mice.…”
Section: Introductionmentioning
confidence: 92%